Evaluation of the attitudes of specialist and family physicians regarding rational drug selection - AKICI, AHMET (KARE PUBL, 2018)
OBJECTIVE: Physicians' personal (P) drugs, which were ranked by priority, may show variations even for the same indication. We aimed to evaluate physicians' knowledge and attitudes regarding P-drug list preparation with respect to the rational use of medicine context. METHODS: A total of 1062 family physicians (FPs) and 562 specialist physicians (SPs) were interviewed and questioned about their knowledge and attitude regarding P-drug list preparation. RESULTS: Compared with SPs (64.9%), significantly more number of FPs (72.8%) prepared a P-drug list. Women were more likely to prepare the P-drug list in both groups; gender comparison showed that significantly more number of female FPs (75.9%) exhibited this attitude than female SPs (67.8%) (p=0.002). Among SPs, the trend for P-drug list preparation attitude decreased with increasing age (p=0.006), and significantly less number of senior physicians showed this attitude compared with junior physicians (p=0.007). The most common source of information referred to by FPs (78.9%) and SPs (74.3%) during P-drug list preparation was pharmaceutical company activities. More than 80% of responders (80.9% of FPs and 83.6% of SPs) specified that a difference exists or partially exists between original and generic drugs. Approximately one in 10 physicians in both groups stated that they rarely/never consider their patients' Iiver/kidney disease during prescribing. CONCLUSION: More prominently in male and senior physicians, the attitude of P-drug list preparation remained lower than expected. Moreover, it is remarkable that pharmaceutical company promotions are the most common source of information for drug selection. These findings disclose the need for the rational use of medicine dissemination interventions for all physicians focusing on more effective use of P-drug list.
Keywords: Family physician; personal drug list; rational use of medicine; specialist physician; COMMON MEDICATIONS; KNOWLEDGE; PERCEPTIONS; DOCTORS; COSTS